Pediatric radiography: how to prepare a child for an imaging procedure - Abd. Aziz, Azian (2016)
Radiation protection in children is very important because their life time exposure to radiation is longer when compared to adult thus the radiation effects that they may encounter would also be much higher. Health care workers need to be aware of this issue and any investigations requiring the usage of ionizing radiation need to be justified. For a proper radiological examination to take place in order to obtain optimized images, a child need to be adequately prepared.